Impact evaluation of research by the International Food Policy Research Institute on agricultural trade liberalization, developing countries, and WTO's Doha negotiations - Hewitt, Joanna (International Food Policy Research Institute, 2008)
This report assesses the impact of IFPRI's work on the agriculture negotiations in the WTO's Doha Round. It is set against the context of IFPRI's mission which emphasizes food security and the interests of poor people in low-income countries and underlines the importance of active engagement in policy communications to link research work to policy action. The report also traces briefly the evolution of IFPRI's work on international agricultural trade more generally, noting its broad disposition to market-oriented policy prescriptions while illuminating the very different impacts of agricultural trade liberalization on individual developing countries through detailed research at the national and household level.